Challenges to well-being for general practice trainee doctors: a qualitative study of their experiences and coping strategies. Issue 1136 (6th March 2020) - Ansell, Sarah; Read, James; Bryce, Marie
Abstract: Purposes of the study: To identify the challenges to well-being experienced by general practice postgraduate trainees and to explore how the trainees respond to those challenges. Study design: Qualitative focus group study with doctors in their final year of general practice training (n=16). The participants in the study were recruited from one training scheme in South West England. Data were thematically analysed. Results: Participants reported challenges to well-being relating to dysfunctional relationships with colleagues and patients, their workload, a perceived lack of support at work and also physical environmental challenges. They identified response strategies focused on cognitive processing, physical self-care, focusing on their professional purpose, building supportive relationships and adapting their working environment where possible. Additionally, there were factors that could support trainee well-being, including personal factors such as adaptability and self-awareness, but also external and organisational factors, such as culture, supportive colleagues and organisational adaptability in relation to workload management. The importance to trainees of the idea of being a 'good doctor' arose repeatedly in the data, as did the importance of the organisational environment. Participants reported finding their training placements in secondary care environments particularly challenging. Conclusion: This research highlights the strategies that general practice trainees use in response to challenges, but also that the responsibility for maintaining well-being cannot be borne by individuals alone. This study identifies that supportive approaches by healthcare organisations and educators are vitally important to general practitioner trainees' well-being.